Protein yield and mineral contents in Pereskia aculeata under high-density planting system - Maria Regina de Miranda Souza (Pesquisa Agropecuária Tropical, 2020)
The development of technologies to increase the yield of Pereskia aculeata Mill. may contribute to its market insertion as an excellent source of protein. This study aimed to assess the influence of plant density on protein yield and mineral contents of P. aculeata leaves and branches. The experiment consisted of five treatments (1 plant m-², 5 plants m-², 10 plants m-², 25 plants m-² and 50 plants m-²), in three blocks. Eight consecutive harvests were obtained over 12 months, and 10 plants m-² was considered the best density, with yields of 144.0 t ha-1 year-1, 25.6 t ha-1 year-1, 310.8 t ha-1 year-1 and 58.3 t ha-1 year-1, respectively for leaf fresh and dry matter, and branch fresh and dry matter. The average leaf protein content (22.4 %) was not influenced by plant density. The estimated total protein yields were 5,759 kg ha-1 year-1 and 9,035.3 kg ha-1 year-1, respectively in the leaves and branches with leaves. The high-density system with 10 plants m-2 in successive harvests is a fast way to produce large amounts of vegetable protein and mineral-rich leaves per area and time for human and animal feeding.